Scaffolding industry knowledge on errors in construction estimates - Olatunji, Oluwole (2011)
The construction industry has had considerable criticisms on inefficiencies in the quality and outcomes of professional services in project delivery. These criticisms have spanned design, estimating, procurement and construction, whilst a range of manifestations of inefficiencies have been reported in forms of errors, conflicts, omissions, mistakes and descriptive ambiguities. Although, there is strong evidence in literature regarding how these issues are triggered and how specific efforts can be targeted at some improved technologies and process-driven solutions in the interest of efficient outcomes, however existing knowledge about the forms of each indicator of inefficiency is somewhat superficial. Specifically, issues such as the complex nature of construction risks, slow uptake of some deliverables of digital innovations, professionalism and ambiguity in clients' requirements have been eloquently argued as common triggers of inadequacies in some outcomes of professional services in the construction industry. This studies reviews different forms of estimate errors in construction.